The Analytical Study of Buddha’s quest for Enlightenment with special emphasis to Suttas of Majjhima Nikaya (Bodhi Path, 2020)
Asceticism has always been part of the spiritual practices even before the Buddha, there used to be a common belief that if one indulges in one’s senses or suppresses them, then one would ultimately reach the purification of mind .So there were two extremes  which were sought after to find satisfaction and peace of mind, one of the extreme  was the sensual indulgence  and another was self mortification practice.So after understanding the limitations of these two extremes, Buddha decided to practice the middle way which avoids both extremes and thus after walking  the middle way he reached to the direct understanding into the real nature of phenomenal world in terms of three characteristics of transitoriness ,suffering and selflessness. Asceticism in Pre Buddhist Period i.e. the Ascetic practices of Three traditions namely- Vedic Religion, Jains (Nigantha Ascetics) and Ajivikas(naked ascetic wanderers) had their influence on Buddha's Quest. Various types of a Ascetic practices of Pre Buddhist era  related to Basic  requisites of  Ascetics (food ,clothing and shelter ) had a deep influence on Buddha's spiritual training  .Buddha after realizing that the extreme self mortification practices are not conducive for achieving the higher goal, also guided other Ascetics  to avoid self mortification  practices as clearly mentioned in  the second Sutta of Patthika Vagga of Digha Nikaya which is  Udumbarika sutta  given to Ascetic Nigrodha who was a wandering Ascetic. Thus this Research paper will deal with the different phases of Buddha's Quest as depicted in Majjhima Nikaya.
Keywords: Enlightenment; Middle way